Glucose diffusion in colorectal mucosa—a comparative study between normal and cancer tissues - Carvalho, Sónia (2017)
Colorectal carcinoma is a major health concern worldwide and its high incidence and mortality require accurate screening methods. Following endoscopic examination, polyps must be removed for histopathological characterization. Aiming to contribute to the improvement of current endoscopy methods of colorectal carcinoma screening or even for future development of laser treatment procedures, we studied the diffusion properties of glucose and water in colorectal healthy and pathological mucosa. These parameters characterize the tissue dehydration and the refractive index matching mechanisms of optical clearing (OC). We used ex vivo tissues to measure the collimated transmittance spectra and thickness during treatments with OC solutions containing glucose in different concentrations. These time dependencies allowed for estimating the diffusion time and diffusion coefficient values of glucose and water in both types of tissues. The measured diffusion times for glucose in healthy and pathological mucosa samples were 299.2+/-4.7 s and 320.6+/-10.6 s for 40% and 35% glucose concentrations, respectively. Such a difference indicates a slower glucose diffusion in cancer tissues, which originate from their ability to trap far more glucose than healthy tissues. We have also found a higher free water content in cancerous tissue that is estimated as 64.4% instead of 59.4% for healthy mucosa.